21st-Century EFL Assessment Innovation: HOTS-Based Evaluation Instruments in an Indonesian Government-Published English Textbook - Yeli Zastika; Syahrul Ramadhan; Yenni Rozimela (Darul Yasin Al Sys, 2026)
Although the distribution of Higher Order Thinking Skills (HOTS) in English language textbooks has received increasing scholarly attention, research specifically examining the cognitive profile of evaluation instruments across six language skills and Genre-Based Approach (GBA) stages in Merdeka Curriculum senior high school textbooks remains limited. This study aims to analyze the distribution of HOTS and Lower Order Thinking Skills (LOTS) in the Grade XI English textbook English for Change and identify gaps in its alignment with 21st-century assessment needs. A mixed-methods sequential explanatory design was employed, involving 211 evaluation instruments selected through total sampling across five units and six language skills. Data were collected using a structured coding sheet and analyzed through descriptive quantitative frequency analysis, followed by descriptive interpretive content analysis. The findings indicate that HOTS accounts for 58.8% of the total evaluation instruments, with Creating (C6) as the most dominant cognitive level (25.6%) and Understanding (C2) as the least represented (6.6%). Writing (77.1%) and Presenting (76.7%) show the highest HOTS proportions, whereas Listening remains LOTS-dominant (52.8%), and all End-of-Unit Reflection instruments are entirely LOTS-based (100%). These findings suggest a productively asymmetric distribution of HOTS that supports learning quality while revealing the need for stronger cognitive scaffolding in critical listening, analytical viewing, and evaluative reflection. Theoretically, this study contributes to the application of Revised Bloom’s Taxonomy in cross-skill textbook analysis and expands understanding of cognitive scaffolding within GBA-based instructional design. Practically, it provides a replicable needs-analysis framework and recommends that textbook developers, teachers, and policymakers strengthen evaluation instruments to better support 21st-century assessment in the Merdeka Curriculum. This study also opens opportunities for comparative research across Merdeka Curriculum English textbooks in Indonesia.